Advocacy Coalition Framework Policy in Halal Certification of Packaging Ink Chemicals - Sugeng Endarsiwi; Harits Hijrah Wicaksana; Agung Edi Rustanto; Suryanto Djoko Waluyo (Neo Journal of economy and social humanities, 2025)
This study aims to analyze the dynamics of halal certification policies for packaging ink chemicals in Indonesia through the Advocacy Coalition Framework (ACF) approach. AFC is used to understand the interactions and learning processes between actors with different belief systems in the implementation of halal policies in the non-food sector. This study uses a qualitative approach with descriptive-exploratory case studies. Data were obtained through in-depth interviews, observations, and documentation studies of BPJPH, MUI, LPH, industry players, academics, and Islamic community organizations. The results show that policy implementation involves a multi-actor coalition that negotiates between normative (sharia compliance) and technical (industrial efficiency) values. BPJPH acts as a policy broker that bridges these interests through formal and informal forums that produce collective policy learning. The effectiveness of implementation is influenced by external factors such as the harmonization of international halal standards (JAKIM, SFDA, ESMA) and global market pressures, as well as internal factors such as institutional reform, service digitalization, and capacity building of LPH. Strategic recommendations include simplifying procedures, cluster certification, auditor training, and the development of a database of hazardous chemicals. Translated with DeepL.com (free version).